(untitled) (Journal of Engineering, 2012)
Buckling analysis of composite laminates for critical thermal (uniform and linear) and mechanical loads is reported here. The objective of this work is to carry out theoretical investigation of buckling analysis of composite plates under thermomechanical loads, and experimental investigation under mechanical loads. The analytical investigation involved certain mathematical preliminaries, a study of equations of orthotropic elasticity for classical laminated plate theory (CLPT), higher order shear deformation plate theory (HSDT) , and numerical analysis (Finite element method), then the equation of motion are derived and solved using Navier method and Levy method for symmetric and anti-symmetric cross-ply and angle-ply laminated plates to obtain buckling load by solving eigenvalue problem for different boundary conditions under different thermo-mechanical loading It Also contained a verification study of these methods with those published by other researchers. The results obtained gives good agreement which shows that maximum percentage discrepancy was 7.6152 %. The experimental investigation is to find mechanical properties at room temperature of glasspolyester such as longitudinal, transverse and shear modulus under tension test. Also, to find critical load that cause buckling under buckling test. Analytical and numerical results of critical buckling load studied the effect of Boundary conditions, No. of layers, No. of half wavelengths in y-direction, lamination angle, aspect ratio ,and thickness ratio on buckling load under different thermo-mechanical loading condition